Morphological, clinical, and molecular profiling of post-polycythemia vera accelerated/blast phase occurring with and without antecedent secondary myelofibrosis - Pelagatti, Laura; Pozzi, Giulia; Cortellazzi, Samuele; Mancini, Cristina; Martella, Eugenia; Pagliaro, Luca; Giaimo, Mariateresa; Roti, Giovanni; Vitale, Marco; Carubbi, Cecilia; Masselli, Elena (Frontiers in Hematology, 2024)
IntroductionPolycythemia vera (PV) is a JAK2-mutated myeloproliferative neoplasm (MPN) characterized by clonal erythrocytosis and an intrinsic risk of transformation into acute myeloid leukemia (AML), known as blast-phase (BP) disease, a condition typified by dismal prognosis. In PV, the evolution to BP generally occurs through an overt fibrotic progression, represented by the post-PV myelofibrotic (MF) stage. However, direct leukemic transformation from PV may also occur in up to ~50% of patients. In this study, we sought to shed light on the morphological, clinical, and molecular features that may differentiate BP arising from a direct transition from the PV stage (post-PV-BP) from those evolving through a diagnosis of post-PV myelofibrosis (post-PV-MF-BP). Methods and resultsWe retrospectively analyzed a cohort of post-PV-BP (n=5) and post-PV-MF-BP (n=5). We found that BP arising from PV directly displayed significantly lower leukocyte count (median 2.93 × 109/L, range: 2.30–39.40 vs. median 41.05 × 109/L, range: 5.46–58.01; P=0.03), and spleen diameter (14.0 cm, range: 11.5–20.0 vs. 25.5 cm, range: 18–26; P=0.03) as compared to those experiencing an overt fibrotic stage. The most striking differences emerged from bone marrow (BM) morphological analysis: all post-PV-BP were characterized by significantly higher cellularity (median 70%, range: 60%–98% vs. 28%, range: 2%–41%, P=0.0245), lower degree of fibrosis (fibrosis grade 1 vs. fibrosis grade 3 in all cases, P=0.008) and dysplastic features involving all three lineages, most prominently the erythroid and megakaryocytic compartment. Next-generation sequencing (NGS) analysis revealed that post-PV-BP cases were enriched in mutations located in genes involved in DNA methylation such as DNMT3A, IDH1/2, and TET2 (45% vs. 15%, P=0.038). DiscussionWith all the limits of the small number of patients for each cohort, our data suggest that BPs that arise directly from PV present a peculiar phenotype, consistent with the molecular signature of the disease, typified by mutations of genes occurring with a high frequency in Myelodysplastic Syndromes (MDS) and MDS/MPN. Further studies in larger cohorts are warranted to translate these observations into robust evidence that may advise therapeutic choices.